The Mechanisms of the Regulation of Immune Response in Patients with Comorbidity of Chronic Obstructive Pulmonary Disease and Asthma - Elena P. Kalinina; Yulia K. Denisenko; Tatyana I. Vitkina; Elena G. Lobanova; Tatyana P. Novgorodtseva; Marina V. Antonyuk; Tatyana A. Gvozdenko; Vera V. Knyshova; Anna V. Nazarenko (Canadian Respiratory Journal)
Background. Comorbidity of chronic obstructive pulmonary disease (COPD) and asthma (asthma COPD overlap syndrome, ACOS) is a significant problem in pulmonary practice, whose pathogenetic issues are not clarified yet. Objective. To study the features of the regulation of immune response in patients with comorbid COPD and asthma. Methods. We assessed the levels of CD3+, CD4+, CD8+, CD4+/CD8+, CD19+, CD25+, HLA-DR, total IgE, TNF-α, IL-4, IFN-γ, TXB2, and LTB4 in patients with comorbid COPD and asthma. Results. The study involved 44 people with COPD, 39 people with asthma, and 12 people with comorbid COPD and asthma. The specific features in comorbid COPD and asthma were lymphocytosis, increased absolute count of T-helper cells, increased cytotoxic T-lymphocytes in relative and absolute count, increased relative and absolute numbers of B-lymphocytes, and high levels of total IgE. The elevated levels of TNF-α and IL-4 and inhibition of IFN-γ production were detected. The content of LTB4 was maximal; TXB2 levels were higher than in control group but lower than in COPD and asthma. Conclusion. In comorbid COPD and asthma inflammation increased even during stable period. High levels of eicosanoids, low production of Th1-type cytokines, and active synthesis of opposition IL-4, along with increased IgE, indicate the activation of Th2-type immune response.